Responses of maximal fat oxidation and Fatmax to incremental exercise and electrical muscle stimulation in overweight men - Minoo Bassami; Shirin Khaknejad; Rasoul Easlami; Ali Nejatian Hoseinpour (Shahid Beheshti University, 2024)
Background and Purpose: Inactive lifestyle has led to an increases in overweight and obesity over the past years, and become an epidemic problem worldwide. Regular exercise is one of the interventions recommended for weight loss and health improvement. The amount of energy consumed during exercise is mainly provided by the combination of fat and carbohydrate metabolism, and the use of these resources depends on the diet, muscle glycogen concentration, and the intensity, duration and type of exercise. During high-intensity exercise, metabolism is more dependent on carbohydrates, while fat is the main fuel during low to medium intensities. Electrical muscle stimulation is an advanced technique which has the ability to create effects similar to the muscle contraction and can increase blood flow to muscles and possibly as a result fat oxidation increases. The present study aimed to investigate the response of maximal fat oxidation (MFO) and Fatmax to incremental exercise and electrical muscle stimulation in overweight men.Materials and Methods: Ten overweight men (age, 29.10±6.08 years, body mass index, 28.49±1.98 kg/m2) voluntarily participated through a formal invitation. The subjects attended the laboratory in two separate sessions. In the first session, they performed an incremental test to determine maximum fat oxidation and VO2max. In the second session, they repeated the same test, with electrical muscle stimulation applied during the exercise test. Respiratory gases were collected to measure fat and carbohydrate oxidations. The test procedures were such that after warming up for five minutes, the subjects started the exercise at an intensity of 50 watts on the cycle ergometer and 25 watts was added to the workload every three minutes, until their respiratory exchange ratio (RER) reached to one. Thereafter, every 2 minutes the workload was increased by 25 watts until volitional exhaustion. Frayn's formula was used to calculate fat and carbohydrate oxidations. The data for MFO and Fatmax were obtained from the stage with the highest fat oxidation and the equivalent intensity was selected.Results: An increase in the amount of Fatmax level was observed in incremental exercise and electrical muscle stimulation (79%±6%) trial compared to the incremental exercise trial (74%±14%), though, the statistical analysis did not show a significant difference between the two trials (P=0.365). Furthermore, no significant differences were observed between the two trials for MFO (P=0.303), fat oxidation (P=0.397) and carbohydrate oxidation (P=0.969).Conclusion: Based on these results, it could be concluded that electrical muscle stimulation combined with incremental exercise can lead to an increase in Fatmax levels in overweight men, but it does not have a significant effect on fat oxidation, carbohydrate oxidation, and MFO.